Kajian Bahasa dalam Konteks Influencer Marketing: Pengaruh Pemakaian Bahasa dalam Pemasaran Akun Selebgram @Fadiljaidi - Ayu Azzahra, Annisya; Azzam Izzuddin; Rana Hanifah, Jihan; Abdirakha Ilham, Muhammad; Br Tarigan, Yola Tarisa; Eni Nurhayati (Economic Reviews Journal, 2024)
In a continually evolving digital landscape, influencers play a pivotal role in shaping consumer behaviors. This research focuses on analyzing the language strategies employed by influencers in their marketing content. From the use of creative language styles to tailored keyword usage, this study highlights how language serves as a primary tool in capturing attention, building brand identities, and influencing audience mindsets. Apart from considering the language strategies utilized by influencers, this study also delves into the impact of language usage on their followers. This analysis sparks a discussion on how audiences perceive various types of language used in influencer marketing content. The influence of language on the perception of promoted products or services and purchasing decisions takes center stage in this research.